The topical application of clofibrate in the treatment of acne vulgaris - Al-Mousilly M. Maiada (College of Pharmacy / Mustansiriyah University, 2005)
Acne vulgaris is a common skin disease. The therapeutic approach to this disease includes standard topical and systemic agents to newly introduced alternative medications. This study suggests a new indication for clofibrate (the lipid lowering agent) & that is to be used topically in the treatment of acne vulgaris. The proposed mechanism is by decreasing lipid biosynthesis which takes place in the sebaceous gland. A total of 60 patients with visible papules and pustules of severe acne were enrolled in this study . Their age range between 13 - 31 years (24 males & 36 females). Healthy age matched controls (30 subjects) without any skin diseases were also participated is this study. Clinical investigations involved disappearance of signs and symptoms of the disease while the biochemical investigations involved measuring total cholesterol, HDL, LDL, & TG levels, SGOT, SGPT in the sera of all volunteers done before and 10 days after the topical application of clofibrate (500mg once daily). The effectiveness of the topical application of clofibrate was approved in the treatment of acne vulgaris as a new clinical application of this drug and a novel strategy for the treatment of the disease as there was significant improvement 75% of the patients & moderate improvement for the rest of the patients . In comparison with controls, patients with acne had higher total serum cholesterol and LDL levels with no significant difference in TG, HDL & enzyme levels. However, after the topical application of clofibrate, total serum cholesterol and LDL levels were decreased while no significant changes observed in the TG, HDL, GOPT, GPT serum levels. The results revealed that circulating lipid were slightly higher in patients with acne than control subjects but declined after treatment. Healing was accompanied with improvement in the symptoms of the disease. This might suggest that the lipid profile is one of the contributing or aggravating factors for this disease.